Analysis of the Effect of Local Magnitude on Peak Ground Acceleration and Seismic Vulnerability Index for Geothermal Field Monitoring Using Microearthquake - Widya Utama; Rista Fitri Indriani; Sherly Ardhya Garini (Postgraduate, University of Mataram, 2023)
Intensive exploitation of geothermal injection and production can trigger microearthquakes which it signals come from dynamic fractures. The purpose of this study is to decide the impact of local magnitude on mitigation in geothermal fields based on soil acceleration and vulnerability of seismic in geothermal fields. This study uses seismic wave recording data and the geology of the research area. It is focable on calculating local magnitude, ground acceleration and seismic susceptibility index to earthquakes based on ground acceleration and seismic susceptibility index in geothermal fields. The maximum amplitude value represent that the medium classification class (3<A0<6) is associated with a moderate degree of deformation. Natural frequency value are found with a moderate classification (4<f0<10) around the area of injection wells and production wells, indicating that the research area has a moderate level of soil hardness structure. The peak ground acceleration in the study area is classified as moderate (0.25<PGA<0.7) which means that the area has a moderate level of risk. Vulnerability of seismic in the study area is included in the low classification (Kg<10). The local magnitude impact on soil acceleration and vulnerability of seismic in this study has a moderate risk and can be categorised as safe. In the future, this research serves as a basis for proper decision-making in geothermal energy operations, monitoring, and infrastructure development